The Maltese falcon [videorecording (Blu-Ray)] - Huston, John, 1906-1987; Bogart, Humphrey, 1899-1957; Astor, Mary, 1906-1987; George, Gladys, 1904-1954; Lorre, Peter; MacLane, Barton, 1902-1969; Greenstreet, Sydney; Hammett, Dashiell, 1894-1961 (Turner Entertainment Co. : Warner Bros. Entertainment : Distributed by Warner Home Video, 2010)
A gallery of high-living lowlifes will stop at nothing to get their sweaty hands on a jewel-encrusted falcon. Detective Sam Spade wants to find out why, and who'll take the fall for his partner's murder.